An Investigation on the Evaluation of the Factors Affecting Brand Love - Unal, Sevtap; Aydın, Hatice (ELSEVIER SCIENCE BV, 2013)
Brand love is a relatively new subject in the marketing literature. As it is known, consumers' establishing emotional bonds with brands and the bond connecting the self with the product-brand are longstanding issues which have an extensive coverage in the literature. It explains the brands specially positioned by the consumer and the characteristics of them. In this study, the effect of social self, variety-seeking and brand image on creating brand love was investigated. Assuming that a loved brand will create brand loyalty and lead to positive word-of-mouth communication (wom), brand love was considered as an intervening variable and the effect of brand love on brand loyalty was aimed to be investigated. Data were collected by means of face-to-face interview method. The questionnaires were administered to the students of Ataturk University. Convenience sampling method was used as a sampling method. Structural Equation Model was used to test the research model. As a result of the research, it was determined that brand image and social self had a positive effect on brand love and that variety-seeking had no significant effect on brand love. Variety-seeking has a negative effect on brand loyalty. Brand love has a positive effect on brand loyalty and word-of-mouth communication. (C) 2013 The Authors. Published by Elsevier Ltd.
Lumen 3rd International Conference on Logos Universality Mentality Education Novelty (LUMEN) - Current Paradigms in Social Sciences -- APR 10-13, 2013 -- Iasi, ROMANIA
Keywords: Variety Seeking; Brand Image; Social Self; Brand Love; Brand Loyalty; Word-of-Mouth